A critical analysis of the treaty-making powers of the union of South Africa and the republic of South Africa - Schaffer, Rosalie Pam (My University, 2015)
lae evolution of the treaty-making power in the Republic has been heavily influenced by the fact that South Africa, as one of the 'older’ British Dominions, acquired independent through a slow but orderly constitutional process. In ■i c first two chapters of this thesis I have ^ therefore attempted to sketch briefly the force at work in South Africa ’“'J n 'tt{ earliest f orm.iti ve years. This ha.-: stalled m examination of c ‘ 1 ; onstitutit i.i 1 ;aw I ssue:. ( nc lud i n fh pr- rogatlve powers of the Crown in relation to treat!c >• and declarai i i.s of war) as well as U problems of internal! nai law. My resear it in th s field led re. to won don and 1111 wva. : of mcttr - il lodged in the various Comr'onweal th mm libraries. In the i i.ir.i and fourth chapters I have concentrated on more immediate matters, namely, th. ■gotiation and conclusion, ratification and implementation of treaties in present-day South Af.lea. The dearth of published in! ormation on th * topic ha necessitated the construction of an overall """* pi.ture by in- in!-tv avii o information obtained fret, the Department ° • ^ Affairs with the views of the International Law Commission as tJ xpr< ssed in the 1969 Vienna C nventiort on the Law of Treaties. It should ^ be i t d that. , ilthough South Africa has not yet ratified the Convention, it recognizes its international validity and attempts, whenever possible, to give effect to its provisions. Chapter five covers th constitutional limitations on the treatyweei making power as well as the inter-relaiionship f international law with "1 municipal law. In both these relat. i ar- as South African practice has be cm moulded n British lines. A a result I have been led to compare — I the law (: -th precedent and principle) in South Xi rica v. . th that of Britain. «J I have attempted to show, too, that the Blacks tone doctrine that 1internation ! law 1 part of the 1 iw o! the land' is not applicable to treaties. ^ A number of States have acquired indepvnd nee in recent years or are in the proce s of doing .o af the present time. With this in mind, an r*t international i • t- rence was convened in Vienna in April, 1977, to discuss succession of State to treaties, and a dtaft convention was formulated. I have included a chapter on the South African approach to succession of *** States to treaties not only because the problem is topical but also fl because it affects the Republic personally'. South Af ri an courts have M been approached on several occasions to decide whether treaties have
A Thesis Submitted to the Faculty of I aw University of Witwatersrand, Johannesburg for the Degree of Doctor of Philosophy Johannesburg 1978
Keywords: Constitutional law and history--South Africa.; Sovereignity.; International law.